Effect of Lactose Pseudopolymorphic Transition on the Aerosolization Performance of Drug/Carrier Mixtures - Andrea Della Bella; Michele Müller; Andrea Danani; Luciano Soldati; Ruggero Bettini (MDPI AG, 2019)
Physico-chemical properties of lactose are key factors in adhesive mixtures used as dry powder inhaler (DPI). Despite the abundant literature on this topic, the effect of the polymorphism and pseudo-polymorphism of lactose has been seldom investigated and discussed although often lactose used in DPI is subjected to unit operations, which may alter its solid-state properties. Here, we studied the aerosolization performance of salbutamol sulphate (SS) or budesonide (BUD) formulations by investigating the effect of lactose pseudopolymorphism in ternary (coarse lactose/fine lactose/drug) and binary (coarse lactose/drug) mixtures. An improvement of the aerosolization performance of SS formulations with the increase of the amount of fine micronized lactose up to 30% (fine particle fraction (FPF) = 57%) was observed. Micronized lactose contained hygroscopic anhydrous α-lactose, which converted to α-lactose monohydrate at ambient conditions. This implied that the positive effect of fines on the aerosolization performance decreased and eventually disappeared with the formulation aging. Positive effect on SS deposition was observed also with binary mixtures with anhydrous lactose, whereas the opposite occurred with budesonide-containing formulations. The collected data demonstrated the crucial role of the carrier crystal form on the positive effect of fines on the deposition.